Investigation of Radioactivity Levels and Radiation Hazards in Soil Samples Collected from Different Sites in Tafila Governorate, Jordan - Al-Qararah, Ahmad M.; Almahasneh, Abdallah H.; Altarawneh, Derar; Jaffal, Alaa (Jordan Journal of Physics, 2025)
Natural and artificial radioactivity levels in surface soil samples collected from various sites in Tafila governorate in Jordan, have been determined using gamma-ray spectrometry. The average concentrations of 238U, 226Ra, 232Th, 40K and 137Cs were 23.6 ± 3.1, 23.3 ± 0.7, 16.7 ± 1.0, 234.1 ± 9.85 and 5.4 ± 0.3 Bq kg-1, respectively. The activity ratio between 238U and 226Ra for all samples was close to unity. The average values of radium equivalent activity, gamma-absorbed dose rate in air, annual effective dose equivalent, external hazard index, internal hazard index and excess lifetime cancer risk were 65.2 Bq kg-1, 30.6 nGy h-1, 37.6 µSv y-1, 0.18, 0.24 and 1.39×10-4, respectively. These values for the collected samples do not exceed the permissible limits. Therefore, the studied area does not pose any significant radiation hazard to the public. Furthermore, it has been found that the activity concentration of 137Cs radionuclide is within the values of recommended safe levels. Keywords: Soil samples, Natural radioactivity, Artificial radioactivity, Gamma-ray spectrometry, Radiation hazard assessment